2016
DOI: 10.1177/2156587216643684
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Hepatitis From the Perspective of Iranian Traditional Medicine

Abstract: Hepatitis is a global health problem, with significant adverse impacts on patients' quality of life. In this study, we aimed to review major resources of Iranian traditional medicine and determine whether the etiology and semiology of hepatitis, in particular chronic hepatitis, in traditional and conventional medicine might be aligned. Through such studies, we might be able to develop new approaches for clinical research to improve our current knowledge on the etiology and treatment of this condition. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…89 Zhu et al 91 proposed that China should take more effective measures to improve study quality, social management, the relief of economic burden for the needed patients, public awareness, evidencebased policies and medicine, super-vision for clinical practice, diagnostics ability and laboratory quality, the compliance of patients, and the quality of traditional Chinese medicine (TCM) in the management of chronic hepatitis B (CHB) infection in years to come. Yousefi et al 92 found that hepatitis is a global health problem, with significant adverse impacts on patients quality of life; acute hepatitis in Iranian traditional medicine is the equivalent to O , ram harr, and chronic hepatitis in Iranian traditional medicine is the equivalent to O , ram solb. The clinical course of hepatitis in Iranian traditional medicine and conventional medicine are similar.…”
Section: Traditional Chinese Iranian and Asian Medicinementioning
confidence: 99%
“…89 Zhu et al 91 proposed that China should take more effective measures to improve study quality, social management, the relief of economic burden for the needed patients, public awareness, evidencebased policies and medicine, super-vision for clinical practice, diagnostics ability and laboratory quality, the compliance of patients, and the quality of traditional Chinese medicine (TCM) in the management of chronic hepatitis B (CHB) infection in years to come. Yousefi et al 92 found that hepatitis is a global health problem, with significant adverse impacts on patients quality of life; acute hepatitis in Iranian traditional medicine is the equivalent to O , ram harr, and chronic hepatitis in Iranian traditional medicine is the equivalent to O , ram solb. The clinical course of hepatitis in Iranian traditional medicine and conventional medicine are similar.…”
Section: Traditional Chinese Iranian and Asian Medicinementioning
confidence: 99%